Menggugah Kearifan Lokal untuk Membentuk Karakter: Strategi Integrasi dalam Pendidikan di Sekolah - Sholehah, Mar’atus; Halim, Hafizoh; Saksitha, Deassy Arestya (Sosial Budaya, 2023)
Menggugah Kearifan Lokal untuk Membentuk Karakter: Strategi Integrasi dalam Pendidikan di SekolahTRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//